The Old English Prefix for-: Evidence of Grammaticalization and Lexicalization - Broz, Vlatko (Array, 2012)
The Old English verb prefix for- has attracted little attention in the literature. Hardly any previous research has been conducted on the Old English prefix for-, except for a rather obsolete monograph on Germanic for/ver (Leopold 1907) and a very short article by Fraser (1975). For- is usually mentioned as one of the seven inseparable verbal prefixes (De la Cruz 1975: 47, Hiltunen 1983: 49, Brinton 1988: 207-8) and has received considerably less elaboration than the other prefixes such as ge-. Even though Quirk and Wrenn (1957: 110) noted that it often involves a shift to perfective aspect, this claim was not pursued in the literature until Broz (2011: 182-190). The prefix for-’s function is typically described as intensificational, especially in meanings that denote loss, deterioration or destruction. The original spatial meaning of this prefix is ‘away, opposite, off’, which could in Old English still be felt in verbs such as forbugan ‘turn away, avoid’ or forweorpan ‘throw away, reject’. However, even in those two examples the resulting combination of the verb and the prefix is not solely spatial but also exhibits some properties of lexicalization and grammaticalization. A more thorough analysis reveals that for- need not be negatively connoted at all, as the following OE example shows: And he sceal husligan unhale and seoce, þa hwile þe se seoca mage and he shall housel infirm and sick then while the sick may þæt husl forswelgan ; the housel for-swallow ‘And he shall housel the infirm and sick, while the sick can swallow the housel’ c1075. colwsigeXa, ÆLet_1_[Wulfsige_Xa]:84.100 The verb forswelgan ‘swallow (up)’ might have been stored as a unit in the mental lexicon and might have lost its negative connotation in isolation, but a number of other corpus examples also point to the bleaching of for-’s negativity and its pure grammatical function as a marker of perfectivity. The aim of this paper is not only to argue whether the prefix for- is lexicalized or grammaticalized, but also to show that the negative or destructive property of for-prefixed verbs is typically present in the semantics of the simplex verb, not the prefix, which only underscores the negative effect of the action that the verb already denotes. References Britnon, Laurel. 1988. The Development of English Aspectual Systems. Aspectualizers and post-verbal particles (Cambridge Studies in Linguistics, 49). Cambridge: Cambridge University Press Broz, Vlatko. 2011. Diachronic Analysis of Aspectual Preverbs and Post-verbal Particles in English, unpublished doctoral dissertation, Zagreb and Leuven de la Cruz, Juan. 1975. “Old English pure prefixes: structure and function”, In Linguistics, 145: 47-81 Fraser, Thomas K. H. 1975. ‘The preverbs for- and fore- in Old English’ In A. Joly and T. Fraser (Eds.) Studies in English Grammar, 17-28. Paris: Editions universitaires.